Effect of acetone-butanol-ethanol (ABE)–gasoline blends on regulated and unregulated emissions in spark-ignition engine. (1st February 2019) - Li, Yuanxu; Ning, Zhi; Lee, Chia-fon F.; Yan, Junhao; Lee, Timothy H.
Abstract: An experimental study was conducted in a port-fuel injection (PFI) spark-ignition (SI) engine fueled with acetone-butanol-ethanol (ABE) and gasoline. 30 vol% ABE blends with different component ratios (A:B:E = 3:6:1, 6:3:1, and 5:14:1), referred to as ABE(3:6:1)30, ABE(6:3:1)30, and ABE(5:14:1)30, were used as test fuels. Additionally, 30 vol% ethanol and 30% vol.% butanol blended with 70 vol% gasoline, referred to as E30 and B30, respectively, were also used as test fuels. Both the regulated emissions, which include unburned hydrocarbons (UHC), carbon monoxide (CO), and nitrogen oxide (NOx ), and unregulated emissions, including acetaldehyde, 1, 3-butadiene, benzene, toluene, ethylbenzene, and xylene (BTEX), were investigated under various conditions. The experiments were conducted at an engine speed of 1200 rpm and at engine loads of 3, 4, 5, and 6 bar brake mean effective pressure (BMEP) under various equivalence ratios ( φ  = 0.83–1.25). The results indicated that ABE(6:3:1)30 had the lowest UHC and CO emissions, with ABE(3:6:1)30 having slightly higher NOx emissions. As for unregulated emissions, B30 showed the highest acetaldehyde emission and ABE(6:3:1)30 had the lowest among all the fuel blends. ABE(3:6:1)30 and ABE(6:3:1)30 showed a reduction in 1, 3-butadiene emission. Regarding the BTEX emissions, an overall reduction was observed for all the fuel blends, with ABE(3:6:1)30 having shown the lowest BTEX emissions among all the test fuels. The results indicate that ABE could be used as a promising alternative fuel in SI engines, owing to the reduction in emissions. Highlights: Unregulated emissions of ABE-gasoline blends were studied using GC/MS and GC/FID. ABE with typical ratio has lower xylene isomers emissions than other test fuels. Additional acetone in ABE-gasoline blend could reduce 1, 3-butadiene emission. ABE-gasoline blend could reduce BTEX emissions.